ANALISIS KESULITAN BELAJAR MATEMATIKA OPERASI HITUNG PERKALIAN SISWA KELAS IV SD NEGERI 4 PULAU RIMAU - Kurnia Safitri; Ramanata Disurya, Tanzimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to describe the difficulties in learning mathematics of multiplication operations of fourth grade students of SD Negeri 4 Pulau Rimau. This study used qualitative methods using a descriptive approach. Data collection techniques in this study were interviews and documentation. The data analysis technique used was according to Miles and Huberman. The results of the study based on the results of interviews and documentation that had been carried out showed that the difficulties in learning mathematics of multiplication operations of fourth grade students of SD Negeri 4 Pulau Rimau were: these difficulties include errors in using the concept of multiplication, lack of multiplication skills (operating) especially in tens and tens numbers, the influence of deskmates which causes students to have difficulty focusing, often being invited to chat and, their memory is not lacking, low interest in learning students because they are often considered difficult and many students do not pay attention (focus) when the teacher explains the material in front of the class, parents of students who do not accompany their children when studying at home because they are busy working and taking care of homework, and errors in understanding problems such as story problems because they are too long and not directly to the point which causes students to be lazy to read so that many students do not get the correct answers.